Break-even maturity as a guide to financial distress - Colin Ellis (Contemporary Economics)
During the recent crisis, lags in the transmission mechanism of economic shocks, together with monetary and fiscal policy, made it difficult to assess the evolving dynamics of creditworthiness. As such, developments in financial markets became a key guide for investors and policymakers in determining the degree of financial distress that borrowers faced, providing a real-time update of market participants’ views. However, simple measures of borrowing costs such as secondary market yields typically ignore differences in debt maturities and hence refinancing risks. This paper describes a new indicator of financial distress – the break-even maturity – that combines these factors. Using financial market data for euro area countries, the break-even maturity is shown to provide an alternative perspective on the absolute and relative risks associated with different borrowers that is distinct from the standard metrics gleaned from bond yields or credit-default swaps. As such, while break-even maturities are ultimately theoretical constructs, they can offer a valuable alternative perspective on how the financing pressures facing distressed borrowers are evolving in real-time.